A new species of sun-spider from sand dunes in Coahuila, Mexico, (Arachnida: Solifugae: Eremobatidae) - Ballesteros, Alfonso; Francke, Oscar F. (Zootaxa, 2007)
A new species of Eremobatinae solifugid, Eremocosta arenarum is described from “Dunas de Bilbao”, Coahuila, Mexico. This is the fourth known species of the montezuma species-group.